Utility of the Ancient Indian Science of Vaastu in Modern Architecture - Utpal Kumar Nandy; Shravani Nandy; Antara Nandy (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2017)
Building construction industry that deals with the basic requirement of shelter is amongst the most vital of all other sectors. Human beings have seen rapid growth and development ever since the onset of civilization. The science of building construction too has touched great unimaginable heights. Attractive designs and textures adorn our dwellings making us feeling proud and happy. At the same time, it is noteworthy that several other elements such as heavenly bodies, nature and supernatural forces all exert their influence on us. The only prudent way out is to strike a chord of harmony with these forces so as to ensure a pleasant living. Vaastu Shastra is that Indian ancient science that provides guidelines to design and maintain a harmonious living condition in the buildings. It therefore becomes imperative to understand and assimilate the Vaastu ideas into modern architecture. Architecture is the art and science of designing spaces. It is aimed at creating comfortable and congenial living conditions for the users. Vaastu Shastra studies help the architect to take a more holistic picture into account. With the help of the case studies, the research article is intended to understand and emphasize the role of Vaastu Shastra and its practical applications.